PENGARUH INTEGRASI TEKNOLOGI DIGITAL DALAM PEMBELAJARAN AKIDAH AKHLAK TERHADAP MOTIVASI BELAJAR SISWA DI MAN 3 KOTA MAKASSAR - Prastianty Lapamu, Rahma; Subaedah; Nur Setiawati; Hasibuddin Mahmud; Rosmiati; Akhmad syahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of digital technology integration in Aqidah Akhlak learning on students' learning motivation at MAN 3 Makassar City. This research employed a quantitative approach with a correlational method. The population consisted of all students at MAN 3 Makassar City, while the sample comprised 80 students selected using cluster sampling from class XI A1, A2, and A3. Data were collected through questionnaires using Likert scales to measure digital technology integration and students' learning motivation. Data analysis included descriptive statistics, Spearman's rho correlation test, and simple linear regression analysis. The results showed that the level of digital technology integration was in the high category (52.5%), while students' learning motivation was in the very high category (86.3%). The correlation test indicated a positive and significant relationship (p < 0.05) with low correlation strength. Regression analysis revealed that digital technology integration had a positive and significant effect on students' learning motivation with a contribution of 7.1% (Y = 36.148 + 0.089X). These findings suggest that digital technology serves as a supporting factor in enhancing learning motivation in Aqidah Akhlak subjects. Keywords: digital technology integration, Aqidah Akhlak learning, students' learning motivation